Optimal low‐carbon scheduling of integrated local energy system considering oxygen‐enriched combustion plant and generalized energy storages. Issue 4 (24th November 2021) - Chen, Changming; Wu, Xiaogang; Ma, Jien; Chen, Yuge; Liu, Shengyuan; Wu, Xinhua; Ji, Qingfeng; Ye, Jieyang; Yang, Li; Lin, Zhenzhi
Abstract: Under the background of carbon neutrality and large‐scale penetration of renewable energy, the integrated local energy system (ILES) has been extensively recognized as an effective way to reduce carbon emissions and improve renewable energy consumption level due to its high energy utilization and multiple energy complementarity. Hence, an optimal low‐carbon scheduling model of ILES considering oxygen‐enriched combustion plant (OECP) and generalized energy storages (GESs) is proposed in this paper to reduce the carbon emissions, improve the renewable energy consumption level and reduce the operating costs of ILES. More specifically, the cooperation mechanism between OECP and power to gas (P2G) is established to maintain a high carbon capture level during peak load periods; the GESs under the background of ILES is modelled, which can make full use of the multiple energy complementarity to improve the renewable energy consumption level of ILES. Case studies are performed on an IES that consists of an IEEE 33‐bus distribution network, a 44‐node district heating network and a 20‐node natural gas network to verify the effectiveness and advantages of the proposed model.